EMT markers in lung adenocarcinoma pleural effusion spheroid cells1. Issue 8 (18th April 2013) - Giarnieri, Enrico; De Vitis, Claudia; Noto, Alessia; Roscilli, Giuseppe; Salerno, Gerardo; Mariotta, Salvatore; Ricci, Alberto; Bruno, Pierdonato; Russo, Giuseppe; Laurenzi, Andrea; Giovagnoli, Maria Rosaria; Ciliberto, Gennaro; et al.
Abstract: Epithelial‐to‐mesenchymal transition (EMT) is a process in which cells undergo a developmental switch from epithelial to mesenchymal phenotype. This process has been related to embryologic morphogenesis but also to cancer progression and metastasis. The aim of the current study was to investigate the expression of EMT‐related markers in adherent and spheroid cell cultures derived from malignant pleural effusions (MPEs) of patients affected by lung adenocarcinoma. On the basis of efficient in vitro propagation, six cases of MPEs were selected and analyzed by immunocytochemistry staining for EMT markers and by RT‐PCR for transcription factors known to orchestrate EMT. EMT markers immunostaining showed in spheroids a statistically significant correlation between the loss of E‐cadherin immunoreactivity and overexpression of N‐cadherin ( P  < 0.001). Likewise loss of EpCAM epithelial marker was coincident with Vimentin overexpression ( P  < 0.001). RT‐PCR analysis of transcription factors Snail, Slug, and Twist showed a highly variable expression, although a general trend to increase was observed. Importantly, in some selected cases it was possible to establish a precise relationship between spheroid formation, EMT switch and increased upregulation of the marker related to cancer stemness such as ALDH positivity. Therefore, MPE‐derived cell cultures, while recapitulating the heterogeneity of lung cancer, are a suitable system to study the mechanisms at the basis of EMT and to understand its relationship with the generation of cancer stem cells. J. Cell. Physiol. 228: 1720–1726, 2013. © 2013 Wiley Periodicals, Inc.